Optimization of leather material filling-plasticizing process using disperse system - Danylkovych, Anatoliy; Sanginova, Olga; Chervinskyi, Vasyl (Eastern-European Journal of Enterprise Technologies, 2016)
The secondorder mathematical model is obtained on the basis of experimental data at the PJSC Chinbar (Ukraine) using experimental design techniques. The model describes the semifinished leather filling plasticizing process adequately. The fillingplasticizing leather material is obtained from cattle raw material using chrome tanning method and slicing the material to 1.5–1.6 mm thickness. The dispersing mixture of natural fats and oils: beef tallow, sunflower oil, and fish oil in a ratio of 1:1.75:2.25 % was used for plasticizing the semifinished material. The nonionic surface active agent was used to emulsify the fats. The diagrams of singlefactor dependencies for simulation models are obtained, and the influence of disperse system ingredients on basic technological properties of the leather material are analysed. The studied ingredients were plasticizer, modified filler, nonionic surfactant. The studied quality parameters were the output area of the semifinished product, the total content of fatty substances in the tanning material and the hardness of material. The software calculation module in the Visual basic for Application environment is developed to automate the calculation of the optimal dispersed system composition. The module allows converting multicriteria task into single criterion task using maximin convolution and HookeJeeves method to solve the optimization task. As a result, the optimum values of the factors that influence the semifinished leather fillingplasticizing process conditions are found. The optimum values of the concentration parameters of disperse system ingredients using multicriteria constrained optimization task of the filling plasticizing process are found. The output area of the leather material with a minimum hardness of 19.0 sN is increased as compared to the control technology by 7.0 % with 115.3, 22.5, 23.9 concentrations in the solution of plasticizer, modified filler and a nonionic surfactant, respectively. In addition, the fatty substances content in the finished material is 7.6 %, that complies with DSTU 311595 “Leather for Garments. General Specifications”. The developed software module can be applied for the optimization of technological processes of composite materials formation.